Facile preparation of loess-coated membranes for multifunctional surfactant-stabilized oil-in-water emulsion separation. Issue 11 (22nd May 2019) - Wang, Xiaoyang; Li, Mouji; Shen, Yongqian; Yang, Yaoxia; Feng, Hua; Li, Jian
Abstract : Underwater superoleophobic loess-coated PVDF membranes were used for efficient oil-in-water emulsion separation as well as multifunctional water remediation. Abstract : Frequent oil spill accidents and industrial wastewater discharge result in severe health and ecological problems to human beings. Generally, industrial wastewater contains not only various kinds of oils, but also water-soluble dyes and heavy metal ions. Elimination of these contaminants in the process of oil/water separation is very important in industrial applications and still remains unsolved. Even though some membranes with underwater superoleophobicity have been extensively used toward oil-in-water emulsion separation, the bulk of them lack the capacity of removing the water-soluble pollutants from water during oil/water separation. Herein, a novel loess-coated polyvinylidene fluoride (PVDF) membrane was successfully fabricated through depositing the loess and sodium alginate suspension onto a PVDF membrane with a vacuum pump. The loess-coated PVDF membrane displayed extraordinary underwater superoleophobicity with oil contact angles larger than 150° and sliding angles smaller than 10° toward different oils, including crude oil with high viscosity. Besides, the loess-coated PVDF membrane can separate various oil-in-water emulsions with separation efficiencies up to 99.6% and flux as high as 910.4 L m −2 h −1 bar −1 . Moreover, the coated membrane retained excellent separation performances even after 10 cycles. In addition, the coated membrane showed outstanding resistance to corrosive liquids, and could separate oil-in-water emulsions in corrosive solutions effectively. Furthermore, the as-prepared membrane displayed outstanding mechanical performance and flexibility. More importantly, the loess-coated PVDF membrane exhibited effective adsorption toward dyes and heavy metal ions. This cost-efficient, environmentally friendly and multifunctional loess-coated PVDF membrane not only allows natural loess resources to be used rationally, but also effectively solves the problems of water pollution.